Integrative transcriptome and proteome revealed high-yielding mechanisms of epsilon-poly-L-lysine by Streptomyces albulus - Wang, Liang; Yang, Hao; Wu, Mengping; Zhang, Jianhua; Zhang, Hongjian; Mao, Zhonggui; Chen, Xusheng (Frontiers in Microbiology, 2023)
ε-poly-L-lysine (ε-PL) is a high value, widely used natural antimicrobial peptide additive for foods and cosmetic products that is mainly produced by S. albulus. In previous work, we developed the high-yield industrial strain S. albulus WG-608 through successive rounds of engineering. Here, we use integrated physiological, transcriptomic, and proteomics association analysis to resolve the complex mechanisms underlying high ε-PL production by comparing WG-608 with the progenitor strain M-Z18. Our results show that key genes in the glycolysis, glyoxylate, and L-lysine biosynthesis pathways are differentially upregulated in WG-608, while genes in the biosynthetic pathways for fatty acids, various branched amino acids, and secondary metabolite by-products are downregulated. This regulatory pattern results in the introduction of more carbon atoms into L-lysine biosynthesis and ε-PL production. Furthermore, transcriptional and translational upregulation of genes involved in the tricarboxylic acid cycle, oxidative phosphorylation, and pentose phosphate pathway also increase the pools of available NADH, ATP, and NADPH. In addition, significant changes in the regulation of DNA replication, transcription, and translation, two component systems, and quorum sensing may facilitate the adaptability to environmental pressure, thus further regulating the ε-PL biosynthesis. This study enables comprehensive understanding of the biosynthetic mechanisms of ε-PL in S. albulus WG-608, while providing a theoretical foundation development of advanced Streptomycetaceae microbial cell factories.